Modelo de aeroelasticidad comparando un puente tipo colgante versus tipo arco, caso río arajuno y su incidencia en el comportamiento estructural - Poveda Riofrio, Jonathan Jair (2022)
Current requirements point out the need to build flexible structures, depending on the geographical location of the bridge, which will be exposed to the effects of wind. The objective of this research work is to apply an aeroelasticity model comparing a suspension type bridge versus arch type, for the case of the Arajuno River and determine the impact on the structural behavior, with the purpose of finding the best alternative to design a bridge in this locality. This research work has a quantitative approach, the research design is non-experimental, because the phenomenon is observed as it occurs in the natural context. A literature search was conducted to establish the theoretical framework considering reliable sources, for the structuring of the conceptual basis of bridges and the phenomenon of aeroelasticity, with its proposed methods of analysis of aeroelastic forces. Subsequently, basic engineering is carried out for the pre-design, a cable-supported bridge is proposed, specifically the suspension bridge type, and another is an arch type bridge, with a lower deck, upper arch and vertical pendants. The 3D modeling of the suspension and arch bridges is carried out using CSI Bridges software, applying the previously obtained aeroelastic loads and the pre-design sections, generating a computational model of the two bridges. The method of statically equivalent loads for wind action is applied to the bridge models proposed. The results indicate that the method of statically equivalent loads causes greater affectation to the structure due to its higher aeroelastic forces in relation to the other two methods. In addition, the bridge that generated less probability of collapse was the arch bridge because its transverse vibration period and the displacement generated in the structure is lower than the values obtained with the suspension type bridge, which indicates that the best bridge alternative in relation to its design, for the case of the Arajuno River, is the arch type bridge.